PEMANFAATAN BUAH NANGKA SEBAGAI CEMILAN OLEH-OLEH KHAS DESA SRI MENANTI - Evanne, Lovia; Saputra, E.; Nesta, A.R.A.; Haq, A.N.; Paramitha, D.; Adelia, N. (Buletin Udayana Mengabdi; Vol 23 No 4 (2024): Buletin Udayana Mengabdi, 2023)
This community service activity is part of the 2023 KKN activities for Muhammadiyah University Kotabumi students which will be held on January 31 2023 – March 2 2023 in Sri Menantiu Village, Tanjung Raja District, North Lampung Regency. This service activity is carried out for the home industry of chips with the aim of increasing the welfare of life and to overcome the abundance of jackfruit in Sri Menanti and Tanjung Raja. By innovating in the form of processed jackfruit into snack chips as a variation of selling chips. The process of making jackfruit chips is assisted by one of the well-known jackfruit chip owners in Sri Menanti village, namely Mrs. Siti. The method of implementing the activity begins with students collecting data through direct observation. The object of observation is direct interviews with related parties, direct practice, and secondary data collection. Keywords: chips, jackfruit, jackfruit chips, fried food, home industry